Termite–gut-associated actinomycetes as biological control agents against phytopathogen Pyrrhoderma noxium - D. Ipek Kurtböke; Harrchun Panchalingam; Cherrihan Adra (Microbiology Australia, 2022)
Brown root-rot disease is caused by phytopathogenic white-rot basidiomycete fungus, Pyyrhoderma noxium. Currently, it is causing significant issues for the Brisbane hinterland in Queensland, Australia and killing many tree species throughout the greater Metropolitan area, including park and street trees located in Shorncliffe, Taringa, New Farm, Eagle Farm, West End, Hamilton, Indooroopilly, Brisbane River, and the City Centre. Brisbane trees being attacked are figs, poinciana, jacarandas, Chinese elms, Moreton Bay eucalypts, kauris, and hoop pines and these include both public and privately owned trees. A joint study between the University of the Sunshine Coast (UniSC) and the Brisbane City Council (BCC) aimed to assess the efficacy of different biological control agents to control infections in the region. In a substudy presented here, termite gut-associated actinomycetes were evaluated to determine their antifungal abilities against the pathogen.